Association between Education and Intra-Regional Variation on Child Marriage in Sub-Saharan Africa - Okechukwu Stephen Chukwudeh; Akpovire Oduaran (MDPI AG, 2022)
Child marriage is a bane to sustainable development, as it has been associated with the prevalence of sexually transmitted diseases, intimate partner violence, and maternal mortality. This study examines the association between education and child marriage is sub-Saharan Africa. A subsample of one thousand, four hundred and sixty-one females, aged 12 years to 18 years was extracted from the 2018 Nigeria Demographic and Health Survey dataset. The independent variables were intra-regional groups and education. The dependent variable was child marriage (<18 years). The associations between intra-regional groups and education on child marriage were examined from the ever-given birth subsample to estimate odds ratios (ORs) and 95% CIs, using binary logistic regression models. There was a positive significant relationship between maternal education (χ2 = 65.5, p < 0.05) and intra-regional ethnic groups (χ2 = 106.58, p < 0.05) on child marriage. The odds were higher among the Hausa/Fulani groups that do not have a formal education (OR = 1.34; p < 0.05), have a poor financial status (OR = 1.67; p < 0.05), and those who had previously terminated a pregnancy (OR = 1.24; p < 0.05). The findings indicate that the intra-regional ethnic group affiliation and the lack of a formal education influences the incidence of child marriage, especially among socio-economically disadvantage females. Interventions aimed at curtailing child marriage should utilize community-based education to engage relevant stakeholders within the grassroots.